The First World War from above and below. Historical aerial photographs and mine craters in the Ypres Salient. (January 2016) - Stichelbaut, Birger; Gheyle, Wouter; Saey, Timothy; Van Eetvelde, Veerle; Van Meirvenne, Marc; Note, Nicolas; Van den Berghe, Hanne; Bourgeois, Jean
Abstract: During the First World War, ancient siege techniques were used in an attempt to break through the stalemate in the trenches. This paper approaches the mine crater war from a completely new perspective and focuses on a landscape-scale approach rather than on fragmented individual sites. Thousands of contemporary aerial photographs have been used as a primary source of information to detect and understand the historical mine crater landscape along the former Western Front in Belgium. The paper presents a methodology for dating war features by means of a time series analysis of aerial photographs, confronting this historical landscape with a high-resolution Airborne Laser Scanning (ALS) dataset. Highlights: A method for non-destructive investigation of conflict landscapes is proposed. Historical aerial photographs are used to map and analyse First World War mine craters. Confrontation between historical photographs and ALS-data shows preservation of conflict landscapes. Analysis of mine craters shows 6 functional and chronological groups.